2010
DOI: 10.1186/1471-2164-11-170
|View full text |Cite
|
Sign up to set email alerts
|

The RST and PARP-like domain containing SRO protein family: analysis of protein structure, function and conservation in land plants

Abstract: BackgroundThe SROs (SIMILAR TO RCD-ONE) are a group of plant-specific proteins which have important functions in stress adaptation and development. They contain the catalytic core of the poly(ADP-ribose) polymerase (PARP) domain and a C-terminal RST (RCD-SRO-TAF4) domain. In addition to these domains, several, but not all, SROs contain an N-terminal WWE domain.ResultsSROs are present in all analyzed land plants and sequence analysis differentiates between two structurally distinct groups; cryptogams and monoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
207
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(212 citation statements)
references
References 70 publications
4
207
0
1
Order By: Relevance
“…SOS1 is crucial for salt stress tolerance and sos1 mutants are hypersensitive to salt stress, thus the interaction with RCD1 provides one more link between salt stress and ROS signalling. RCD1 is able to interact with several transcription factors in yeast 2-hybrid analysis (Jaspers et al, 2009;Jaspers et al, 2010b). This together with physiological data makes RCD1 a promising candidate as a central integration node for ROS signalling and indicates that highly divergent perception mechanisms, such as those described here for highlight, salt, dehydration (stomatal), and herbicide induced stresses, all converge into a common pathway (Jaspers et al, 2009;Jaspers et al, 2010a;Jaspers & Kangasjärvi, 2010).…”
Section: Enzymementioning
confidence: 92%
“…SOS1 is crucial for salt stress tolerance and sos1 mutants are hypersensitive to salt stress, thus the interaction with RCD1 provides one more link between salt stress and ROS signalling. RCD1 is able to interact with several transcription factors in yeast 2-hybrid analysis (Jaspers et al, 2009;Jaspers et al, 2010b). This together with physiological data makes RCD1 a promising candidate as a central integration node for ROS signalling and indicates that highly divergent perception mechanisms, such as those described here for highlight, salt, dehydration (stomatal), and herbicide induced stresses, all converge into a common pathway (Jaspers et al, 2009;Jaspers et al, 2010a;Jaspers & Kangasjärvi, 2010).…”
Section: Enzymementioning
confidence: 92%
“…Land plants, however, have several types of PARPs and PARP-like proteins, including a novel group of PARP proteins, the SRO family ( Fig. 1A, B; (Citarelli et al, 2010;Jaspers et al, 2010b)). Although first identified in Arabidopsis thaliana (Belles-Boix et al, 2000), these proteins are found throughout land plants and consist of two subgroups (Citarelli et al, 2010;Jaspers et al, 2010b).…”
Section: The Sro Familymentioning
confidence: 99%
“…Kim, 2005). However, other members of the PARP superfamily have been shown to have either mono(ADP-ribose) transferase (mART) activity (Kleine et al, 2008) or to be enzymatically inactive (Aguiar et al, 2005;Jaspers et al, 2010b;Kleine et al, 2008;Till et al, 2008). Biologically, PARP superfamily members are involved in a broad range of functions, including DNA damage repair, cell death pathways, transcription and chromatin modification/remodeling (reviewed in ).…”
Section: The Sro Family: a Novel Group Of Poly(adp-ribose) Polymerasementioning
confidence: 99%
“…Recently, reviews and novel contributions have shed light on the PARP superfamily [5] in all kingdoms of life [6][7][8]. In plants, three PARP proteins and several PARP domain proteins have been described [9].…”
mentioning
confidence: 99%
“…PARP-domain proteins, such as radical-induced cell death 1 (RCD1), have been shown to possess antiviral activity or to be involved in plant response to virus infection. In particular, plants' response to ozone stress or reactive oxygen species (ROS) is dependent on radical cell death 1 (RCD1) and on proteins Similar to RCD One (SRO) to protect the plant from radicals [8,9], and their mutations lead to stress-induced morphogenetic response (SIMR) and developmental defects. Which of the PARP proteins is necessary in plants to protect them from abiotic and biotic stress was a question solved very recently.…”
mentioning
confidence: 99%